ANALYSIS OF WATER INFRASTRUCTURE MANAGEMENT BY AGENCE DES MUSULMANS D'AFRIQUE IN THE RURAL COMMUNE OF KANEMBAKACHE, NIGER - (:unkn) unknown (My University, 2023)
A secular country since its independence, Niger has been experiencing a strong movement towards re-Islamization. This phenomenon, which affects the whole sub-region, is not new, but has accelerated in recent years. In the space of a generation, Islam has invaded the entire public space in Niger. This is the context in which the Agence des Musulmans d'Afrique (AMA) operates in Niger. It works in the fields of Islamic development, but also through the construction of hydraulic infrastructures. These projects are designed to support communities in their search for water to improve their well-being, in the form of “Allah's grace or saboda Allah in the local language”. The aim of this article is to analyze the impact of the management of this free water service in a state that advocates the “user pays” principle. A qualitative survey was carried out in four (4) villages in the rural commune of Kanembakache. The data collected provided not only an overview of the infrastructure, but also an understanding of its operation. The systems cover twelve (12) villages for a population of seventeen thousand seven hundred and thirty-five (17,735) inhabitants, i.e. 19% of the commune's population in 2022. While this coverage is not negligible, the mode of intervention and management is not in line with Niger's water policy. The villages have no management committee. The commune does not know the quality of the water, nor does the technical department. Consumption is not monitored. There are also a number of problems, including disorder around water points, water wastage and even fights.
Keywords: African Research